The symmetrical architecture of Malay simplex forms - Zuraidah Mohd. Don (Journal of Modern Languages)
This paper examines the structure of Malay words, concentrating on simplex forms with no affixation, and analyses over 6,400 simplex forms extracted from a corpus of about 3M words of written Malay. Over 80% of simplex forms are found to fit a template of the structure CV(C)CVC. Examination of the templates links the widespread view that Malay has a ‘simple phonology’ to an inadequate separation of abstract lexical representations and acoustic events in speech waveforms, and the claim is made that this separation is the key to understanding contemporary dialect variation.